Effect of ApoE ε4 gene polymorphism on the correlation between serum uric acid and left ventricular hypertrophy remodeling in patients with coronary heart disease - Liu, Jia; Zheng, Mei-Li; Chen, Mulei; Li, Kuibao; Zhu, Xiaoming; Gao, Yuanfeng (Frontiers in Cardiovascular Medicine, 2022)
Background Hyperuricemia and dyslipidemia are associated with left ventricular hypertrophy (LVH), while the effect of ApoE gene polymorphism on the correlation between serum uric acid (UA) level and severity of LVH in patients with coronary heart disease (CHD) has not been clarified. Methods This was a retrospective observational study of patients with CHD. Patients were divided into groups of ε4 carriers and non-ε4 carriers based on sanger sequencing. The association of ApoE ε4 gene polymorphism, serum UA level, and LVH, determined by cardiac color Doppler ultrasound, was evaluated by multivariate analysis. Results A total of 989 CHD patients who underwent ApoE genotyping were enrolled and analyzed. Among them, the frequency of the ApoE ε4 genotype was 17.9% (15.7% for E3/4, 1.1% for E4/4, and 1.1% for E2/4). There were 159 patients with LVH, 262 with end-diastolic LV internal diameter (LVEDD) enlargement, 160 with left ventricular ejection fraction (LVEF) reduction, and 154 with heart failure. Multivariate analysis showed that for every increase of 10 μmol/L in serum UA level, the risk of LVH decreased in ε4 carriers (odds ratio (OR) = 0.94, 95% confidence interval (CI): 0.890–0.992, P = 0.025) and increased in non-ε4 carriers (OR = 1.03, 95% CI: 1.005–1.049, P = 0.016). The risk of LVEDD enlargement tended to decrease in ε4 carriers (OR = 0.98, 95% CI: 0.943-1.023, P = 0.391) and increased in non-ε4 carriers (OR = 1.03, 95% CI: 1.009–1.048, P = 0.003). The risk of LVEF reduction was reduced in ε4 carriers (OR = 0.996, 95% CI: 0.949–1.046, P = 0.872) and increased in non-ε4 carriers (OR = 1.02, 95% CI: 0.994–1.037, P = 0.17). The risk of LVEDD enlargement decreased in ε4 carriers (OR = 0.98, 95% CI: 0.931–1.036, P = 0.508) and increased in non-ε4 carriers (OR = 1.02, 95% CI: 0.998–1.042, P = 0.07). Conclusion High serum UA levels decreased the risk of LVH in ApoE ε4 carriers with CHD, while increased the risk of LVH in non-ε4 carriers.